2021
DOI: 10.1200/jco.2021.39.15_suppl.9004
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker tissue journey among patients (pts) with untreated metastatic non-small cell lung cancer (mNSCLC) in the U.S. Oncology Network community practices.

Abstract: 9004 Background: Given the importance of molecular testing and targeted therapy for mNSCLC, the MYLUNG (Molecularly Informed Lung Cancer Treatment in a Community Cancer Network) consortium pragmatic study assessed real-world biomarker testing rates and turnaround times (TAT) within The US Oncology Network of over 1,000 providers across the United States. Methods: This was a retrospective observational chart review study of pts with mNSCLC initiating first-line (1L) systemic therapy between 04/01/2018 and 03/3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 0 publications
3
23
1
Order By: Relevance
“…Compared with other countries, Spain accounts for a similar global positivity rate, as the 42% observed in an Italian study 10 and 42.9% in a German study 11 , as well as individually the positivity rates by biomarker. Likewise, determining at least one biomarker is similar to the German experience and to the real-life data reported from the USA 12 .…”
Section: Discussionsupporting
confidence: 67%
“…Compared with other countries, Spain accounts for a similar global positivity rate, as the 42% observed in an Italian study 10 and 42.9% in a German study 11 , as well as individually the positivity rates by biomarker. Likewise, determining at least one biomarker is similar to the German experience and to the real-life data reported from the USA 12 .…”
Section: Discussionsupporting
confidence: 67%
“…When an oncogene-based therapy is identified, a number of these subtypes have a prevalence of less than 5%. Additionally, a recent analysis showed that less than 50% of patients with metastatic NSCLC do not have their tumors tested broadly for genomic aberrations, missing treatment opportunities with small molecules [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the Spanish Lung Cancer Biomarker Testing Registry study, ALK was not tested in 20% of cases, and ROS1 was not tested in over 40% of cases [23]. The situation is similar in the USA, as shown by a recent study by the MYLUNG Consortium TM , which demonstrated that most patients (90%) received testing for at least one out of five biomarkers (EGFR, ALK, ROS1, BRAF, and PD-L1) prior to first-line therapy, whereas less than half had testing for all five [24]. In this study, the median time from diagnosis to first-line therapy was approximately five weeks, and the turnaround time from testing orders to results was approximately two weeks.…”
Section: How Many Patients Miss Out On Biomarker Testing/molecular Di...mentioning
confidence: 72%